Russian speakers in post-Soviet Latvia : discursive identity strategies - Cheskin, Ammon (Russian language and society., 2016)
A theoretical and empirical study of discourse among Russian-speakers in Latvia. The political shocks of the 2014 Ukrainian crisis have been felt in many former Soviet countries, not least Latvia, where over 35% of the population are native Russian speakers. At a time when analysts and commentators are unsure about Russia's future plans to intervene on behalf of their 'compatriots', this study provides a detailed political and cultural analysis of Russian-speaking identity in Latvia. By using Russian-speakers in Latvia as a specific case study, this volume also offers a fresh methodological approach to the study of discourses and discursive strategies. It outlines a coherent methodology to study the evolution of discourses over time, rather than a single de-contextualized and static time period. Drawing on media analysis, elite interviews, focus groups and survey data, Russian Speakers in Post-Soviet Latvia situates the identity strategies of Russian speakers within the political, cultural, and economic transformations of the post-Soviet era. By assessing political, cultural, and economic links with their home state (Latvia) and their potential kin-state (Russia), it offers important insights into the complex identity positions of Latvia's Russian speakers, and how these positions have evolved in Latvia since the late Soviet period. In a time when many will question the loyalty of Russian speakers to their various 'host states' this book provides a timely, scholarly account of ethnic politics in Latvia. It also offers a methodological framework that allows for the mapping of trends in discursive strategies, exploring how they evolve through time. Key Features Uses focus-group interviews, elite interviews, survey data and critical discourse analysis to focus study discourses Features a case study of Russian speakers in Latvia to add to the debate surrounding the status of Russian speakers outside Russia Focuses on the temporally contingent nature of discourse - discussing discursive change and the possibility that a discourse can exist